Improving Student Motivation and Learning Outcomes through the Application of the Cooperative Script Model in Financial Accounting Learning - Abdul Rauf (Universitas Negeri Makassar, 2021)
Cooperative learning is a group learning model that has certain rules. The basic principle of this learning is that students form small groups and teach each other to achieve a common goal. The cooperative script model is a learning method in which students work in pairs and take turns orally summarizing the parts of the material being studied. The main objective of this research is to increase motivation and learning outcomes in learning Financial Accounting in class XII AKL C SMKN 1 Luwuk. The design of this research is classroom action research (CAR). The types of data in this study are qualitative data and quantitative data. Qualitative data were collected by using observation sheets, while quantitative data were collected by giving a test at the end of each cycle. Data analysis in this study is to reduce data, present data, and verify or draw conclusions. The results of this study indicate that the application of the Cooperative Script model can increase student motivation and learning outcomes in learning Financial Accounting in class XII AKL C SMKN 1 Luwuk in the 2021/ academic year 2022.